Amyloid-β (Aβ)-Related Cerebral Amyloid Angiopathy Causing Lobar Hemorrhage Decades After Childhood Neurosurgery. Issue 8 (30th June 2022) - Kellie, Jeremy F.; Campbell, Bruce C.V.; Watson, Rosie; Praeger, Adrian J.; Nair, Girish; Murugasu, Anand; Rowe, Christopher C.; Masters, Colin L.; Collins, Steven; McLean, Catriona; Yassi, Nawaf
Abstract : Background: Recent reports raise the possibility of cerebral amyloid angiopathy (CAA) leading to intracerebral hemorrhage in young adults following childhood neurosurgery, suggesting transmission of amyloid-β (Aβ) through neurosurgical procedures including dura mater grafting. Parenchymal Aβ deposition, and to a lesser extent tau aggregation, similar to that seen in Alzheimer disease, have also been described. Methods: We conducted a database review of 634 consecutive intracerebral hemorrhage patients aged <65 years at a tertiary stroke center over 20 years to identify such patients. Results: We identified 3 patients aged in their thirties who presented with spontaneous lobar intracerebral hemorrhage, with imaging or neuropathology consistent with CAA, and a history of childhood neurosurgery. Two of these patients had undergone a dural repair using cadaveric dura mater (Lyodura). In addition to CAA, both patients had neuropathologically confirmed parenchymal Aβ and tau deposits, characteristic of Alzheimer disease. Conclusions: Our findings support the concept of neurosurgical Aβ transmission but suggest that such cases are rare in standard clinical practice.